Reflexives are Results of Impoverishment - Yoda, Yusuke (Investigationes Linguisticae, 2020)
For decades, the central issues surrounding Binding have been investigation of mechanisms of co-referentiality. Most of literature have attempt to find out the mechanisms of binding condition (Chomsky 1981, 1986). This paper will shed new light on the Binding, that is morphological aspects of reflexive anaphors and pronouns, and the source of subject orientation. The purposes of this paper are to claim that Apparent ses (Pica (1985)) in some languages are in fact pronoun and the subject orientation is emerged as a result of person/gender-feature (φ-feature) impoverishment (cf. Noyer (1997), Halle (1997)). To claim these, this paper looks at Thai and Japanese data. The organization of this paper from next chapter is as follows. Section 2 briefly reviews binding theory we adopt. Then section 3, Thai binding data are introduced. Based on Thai data provided in section 3, section 4 provides proposal and analysis, in which the morpho-semantic framework by Middleton (2018) is introduced. Section 5 shows the current account is also applicable to Japanese reflexives. Section 6 concludes this paper.